Body Image, Physical Activity and Sport Involvement: A Study on Gender Differences - Leng Ho Keat; Phua Yi Xian Philip; Yang Yifan (Sciendo, 2020)
The aim of this study is to examine whether sport involvement i.e. identification with the domain of sports affect satisfaction with body image in men and women. 158 respondents from a tertiary educational institution provided data on their satisfaction with their body image, level of sport involvement, and level of physical activity. Independent t-tests were conducted to compare differences between and within genders. Female respondents (n=40) who were high in sport involvement reported a significantly lower level of dissatisfaction with their body image (M=.55, SD=.78) when compared to female respondents (n=44) who were low in sport involvement (M=.84, SD=.83; t=1.65, p<.05). There was no significant difference amongst male respondents. There was also no significant difference in satisfaction with body image across groups with varying levels of physical activity. This suggests that being involved in sport can affect body image satisfaction amongst females.